The Representation of Gender Equality in Nyai’s Religious Authority at Annuqayah Islamic Boarding School - Syarifuddin; Elliyatul Munawwarah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This research discusses the role and authority of Nyai in Pesantren Annuqayah as a representation of gender equality in the pesantren environment. Traditionally, Nyai is often considered only as a companion of kiai in a subordinate position. However, in Pesantren Annuqayah, Nyai, especially Nyai Fadhilah, occupies a strategic position in decision-making, education, the pesantren economy, as well as being an influential public figure in the community. This study uses a qualitative method with semi-structured interview techniques to Nyai Fadhilah and female santri. The findings show that Nyai not only carries out domestic roles as a wife and mother, but also has religious authority and leadership equal to kiai, both in the internal structure of the pesantren and in the public sphere. In addition, Nyai Fadhilah's leadership in literacy and the environment strengthens women's contribution in the social and religious transformation of pesantren. Using the theoretical approach of Marxist feminism and Radical feminism, this research shows that Pesantren Annuqayah is able to become a model of gender-responsive and inclusive pesantren. This proves that pesantren is not only a place for the reproduction of conservative thinking, but also a potential space for progressive reinterpretation of religious values.